Inventory Management as a Driver of Supply Chain Performance in Agricultural Value Chains: A Lean Theory Perspective from Kenya - Enock Musau Gideon (Agricultural Science, 2026)
Inventory management is a critical supply chain practice with significant implications for supply chain performance, especially in agricultural value chains that face challenges of perishability, demand fluctuations, and resource constraints. Guided by Lean Theory, this study examined the effect of inventory management on supply chain performance within Kenya’s agricultural supply chains using a quantitative explanatory research design. Primary data were collected through a structured questionnaire administered to employees across agricultural directorates. Reliability analysis confirmed strong internal consistency (α = 0.743 for inventory management; α = 0.850 for supply chain performance). Principal component analysis validated construct measurement (KMO = 0.769, p < 0.001). Regression results showed that inventory management significantly and positively predicts supply chain performance (β = 0.265, t = 6.120, p < 0.001), highlighting its role as a key determinant of efficiency and competitiveness. The study concludes that inventory management practices such as vendor-managed inventory, just-in-time replenishment, and stock transparency are indispensable for enhancing supply chain performance in Kenya’s agricultural sector. It recommends that policymakers and managers invest in Lean-inspired inventory strategies to optimize resource use, reduce waste, and build resilient agricultural supply chains.